2012
DOI: 10.1590/s1415-43662012000600002
|View full text |Cite
|
Sign up to set email alerts
|

Características agronômicas e químicas das variedades de cana-de-açúcar RB83-5486 e RB86-7515 sob irrigação e sequeiro

Abstract: R ESU M OObjetivou-se, neste trabalho, avaliar as características agronômicas e a composição química de variedades de cana-de-açúcar sob irrigação e sequeiro colhidas em final de safra. O delineamento experimental foi bloco ao acaso, com seis repetições, duas variedades (RB83-5486 e RB86-7515), em dois ambientes: irrigado e sequeiro. As produções de colmo e matéria seca foram favorecidas pela irrigação, com destaque para a RB86-7515. Maiores teores de proteína bruta, fibra em detergente ácido, celulose e menor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…For Gonçalves (2008), sugarcane stem diameter is affected negatively by water deficiency in the initial phase of development. Macêdo et al (2012), studying the varieties RB835486 and RB867515 under different water regimes, observed that stem diameter varied according to the environment and the variety; also, it was found that the highest productive potential of the varieties was expressed in irrigated conditions.…”
Section: Resultsmentioning
confidence: 99%
“…For Gonçalves (2008), sugarcane stem diameter is affected negatively by water deficiency in the initial phase of development. Macêdo et al (2012), studying the varieties RB835486 and RB867515 under different water regimes, observed that stem diameter varied according to the environment and the variety; also, it was found that the highest productive potential of the varieties was expressed in irrigated conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The NMP of sugarcane crops grown under the Aw and Am climate conditions ranged from 58.8 to 136.9 t ha -1 and 116.79 to 192.91 t ha -1 , respectively (Capone, Lui, Silva, Dias, & Melo, 2011;Oliveira et al, 2011). Macêdo et al (2012) evaluated two sugarcane cultivars in a Cwa climate under irrigated and rainfed conditions during the drought period, where the highest NMP (103.0 t ha -1 ) was observed in the irrigated cultivation. In the same study, the RB83-5486 cultivar had an NMP of 84.0 t ha -1 under irrigated conditions (Macêdo et al, 2012), while in the present study, its NMP was 250.16 t ha -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies concerning the yield and technological attributes of sugarcane have been conducted in different climates, including As (Abreu, Silva, Teodoro, Holanda, & Sampaio, 2013), Aw (Cruz et al, 2010;Rhein et al, 2016), Awi (Caione et al, 2011), Cfa (Schwerz et al, 2017), and Cwa (Macêdo et al, 2012). However, information regarding the behavior of the sugarcane plant under Af climate conditions, which is characterized by abundant rainfall throughout the year and no dry season, is still required.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in different production environments have demonstrated increment in the stalk yield of sugarcane genotypes in response to irrigation (Carvalho et al, 2009;Gava et al, 2011;Oliveira et al, 2011;Macêdo et al, 2012;Silva et al, 2014). However, for the genotype-environment interaction, it is crucial to conduct tests aiming at the expression of the productive potential of the sugarcane cultivars in different water regimes and production environments (Silva et al, 2008).…”
Section: Introductionmentioning
confidence: 99%